ENZYMATIC HYDROLYSIS WITH Saccharomyces cerevisiae FOR ETHANOL PRODUCTION FROM MULI BANANA PEEL (Musa acuminata Linn) - Julianto, Faisal Reja; Kartika, Rudi; Ruga, Ritbey (JURNAL ATOMIK, 2019)
Ethanol production from starch of muli banana peel by enzymatic hydrolysis with the addition of gelatin as a fermentation nutrient for Saccharomyces cerevisiae was done. This research consists of hydrolysis, fermentation, distillation and testing carried out by Gas Chromatography. This research was conducted to determine the optimal time and the optimum nutrient concentration, that can be seen that the optimum time at 7 days and the optimum nutrient concenctration in addition of 2% nutrient with ethanol concentration of 36.344%.